Optimal concentration of ropivacaine for brachial plexus blocks in adult patients undergoing upper limb surgeries: a systematic review and meta-analysis - Wu, Lin; Zhang, Weiyi; Zhang, Xiangdong; Wu, Yinglong; Qu, Hua; Zhang, Donghang; Wei, Yiyong (Frontiers in Pharmacology, 2023)
Aim of the Study: Brachial plexus block (BPB) is widely used for patients undergoing upper limb surgeries. Ropivacaine is the most commonly used local anesthetic for BPB. This study aimed to identify the optimal ropivacaine concentration for BPB in adult patients undergoing upper limb surgeries. Materials and Methods: PubMed, Embase, the Cochrane Library, and Web of Science were searched to identify randomized controlled trials (RCTs) that compared the effects of different concentrations of ropivacaine for BPB in adult patients undergoing upper limb surgeries. The primary outcomes were the onset time of sensory and motor block. RevMan 5.4 software was used for analysis. The GRADE approach was used to assess evidence quality. Results: Nine studies involving 504 patients were included. Compared to 0.5% ropivacaine, 0.75% ropivacaine shortened the onset time of sensory (WMD, -2.54; 95% CI; -4.84 to -0.24; P＜0.0001, moderate quality of evidence) and motor blockade (WMD, -2.46; 95% CI, -4.26 to -0.66; P = 0.01; moderate quality of evidence). However, 0.5% and 0.75% ropivacaine provided similar duration time of sensory (WMD, -0.07; 95% CI, -0.88 to 0.74; P = 0.81; high quality of evidence) and motor blockade (WMD, -0.24; 95% CI, -1.12 to 0.65; P = 0.55; high quality of evidence), as well as time to first request for oral analgesia (WMD, -1.57; 95% CI, -3.14 to 0.01; P = 0.5; moderate quality of evidence). Conclusions: Moderate-quality evidence suggested that, in terms of the onset time of sensory and motor blockade, 0.75% ropivacaine is a preferred concentration for BPB in upper limb surgeries.